PENGARUH LAYANAN INFORMASI TENTANG PENANAMAN NILAI-NILAI KARAKTER TERHADAP PENINGKATAN ETIKA PERGAULANSISWA KELAS X IPS 1 SMA N 2 PEKANBARU - Eta Aulia Rahmi; Tri Umari; Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study purpose to determine how much effect and differences in the provision of information services on the character values of the association ethics students class X social 1 senior high school 2 Pekanbaru before and after the service. The subjects were all students of class X social 1. This study using a quasi experimental design with one-group pretest-posttest, the measurement is performed twice, at the beginning and end. Result of study showed that 65.625% of students are in the unfavorable category before given service . After being given the service an increase 84.375% into the category quite well. This study showing that there are differences in the association ethics class X social 1 senior high school 2 Pekanbaru before and after the implementation of the information service about the character values with the effect of 42.3%.Keywords: Service Information, Character Values, Ethics association